Strategi Mengatasi Permasalahan Penjualan Ayam Penyet pada Usaha Kuliner Lokal - Armina Khoiriyah Nasution; Hafidatul Husna; Meilan Sri Desfitra; Rezeki Putri Utami; Zahwa Aulia (CV. ITTC INDONESIA, 2026)
The ayam penyet culinary business is currently facing several problems that have led to a decline in sales levels and customer satisfaction. Increasingly intense competition with other ayam penyet businesses and similar culinary ventures in the surrounding area provides consumers with many alternative choices, making customer loyalty difficult to maintain. In addition, suboptimal service quality, particularly due to a lack of employee training in service and hygiene, has also affected the business image in the eyes of consumers. Another significant issue is the underutilization of social media as a digital promotional tool, resulting in limited marketing reach and low public awareness of the business. This article aims to analyze the sales problems of the ayam penyet business using SWOT analysis to identify internal and external factors influencing business performance. The research method employed is qualitative descriptive, conducted through observation and interviews. The results of the analysis are expected to serve as a basis for formulating business development strategies, especially in improving service quality and utilizing digital promotion to strengthen the competitiveness of the ayam penyet business.